2019
DOI: 10.1155/2019/3205971
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and Substantivity Properties of Silver Nanoparticles against Oral Microbiomes Clinically Isolated from Young and Young-Adult Patients

Abstract: The dental plaque is an oral microbiome hardly associated to be the etiological agent of dental caries and periodontal disease which are still considered serious health public problems. Silver nanoparticles (AgNPs) have demonstrated to have good antimicrobial properties affecting a wide variety of microorganisms, including oral bacteria; however, there is no scientific information that has evaluated the antimicrobial effect of AgNPs against clinical oral biofilms associated with dental caries and periodontal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 65 publications
(79 reference statements)
2
36
0
4
Order By: Relevance
“…It has been reported that heparin derived from certain fish exhibits antimicrobial activity against bacterial and yeast species at high concentrations [54], but the exact mechanism is not clear. Also, this is not in accordance with the results observed in this study, because even at high concentrations, heparin did not exhibit any antifungal effect.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that heparin derived from certain fish exhibits antimicrobial activity against bacterial and yeast species at high concentrations [54], but the exact mechanism is not clear. Also, this is not in accordance with the results observed in this study, because even at high concentrations, heparin did not exhibit any antifungal effect.…”
Section: Discussionmentioning
confidence: 99%
“…The antimicrobial efficacy of nanosilver is inversely proportional to the size of silver nanoparticles [ 15 ]. Silver nanoparticles with smaller diameter present better biofilm inhibition results than larger particles [ 31 ] and are effective against S. mutans [ 33 ] and Streptococcus orallis biofilms [ 88 ]. However, larger AgNPs were also demonstrated to have significant antimicrobial activities against a wide variety of dental plaque microorganisms, showing acceptable bacterial growth inhibition even at lower concentrations [ 31 ].…”
Section: Silver Nanoparticles and Dentistrymentioning
confidence: 99%
“…Silver nanoparticles with smaller diameter present better biofilm inhibition results than larger particles [ 31 ] and are effective against S. mutans [ 33 ] and Streptococcus orallis biofilms [ 88 ]. However, larger AgNPs were also demonstrated to have significant antimicrobial activities against a wide variety of dental plaque microorganisms, showing acceptable bacterial growth inhibition even at lower concentrations [ 31 ]. Biologically synthesized AgNP (using neem, onion, and tomato in the synthesis process) with sizes considered large (26.2 to 33.3 nm) showed antimicrobial activity against S. aureus , possibly due to the high concentration of flavonoids and terpenoids [ 75 ].…”
Section: Silver Nanoparticles and Dentistrymentioning
confidence: 99%
See 2 more Smart Citations